Analisis Dampak SE Menpan RB No1 Tahun 2021 Terhadap Kinerja Keuangan Perusahaan Sektor Telekomunikasi - Randy Heriyanto (Akuntansi dan Manajemen, 2022)
In this day and age, people are starting to adjust to the new normal order of life while going through the COVID-19 pandemic. In 2020, people suddenly adjusted the flow of work that is usually done in the office to be at home, known as Work from Home. However, this change has begun to be adapted by the community in 2021. People have started doing office work or at home in accordance with the regulations of their respective agencies. This regulation is also emphasized in the imposition of restrictions on community activities regarding the enforcement of ASN employee discipline. During 2020, people have used internet services to support work done at home. By adapting to the new normal, it is possible for employees to work in the office by prioritizing health and safety. The purpose of this research is to look at the differences in the financial performance of companies in the information technology sector as internet service providers due to the SE Minister of PAN-RB No.1 of 2021. In this study, differences in financial performance were found, namely during the pandemic, namely in the Total Asset Turnover section which had an effect on significant during the COVID-19 pandemic in the second year. The results found are companies engaged in the telecommunications sub-sector can earn high profits with their assets